Domperidone for insufficient lactation in England 2002‐2015: A drug utilization study with interrupted time series analysis. Issue 12 (14th August 2018) - Mehrabadi, Azar; Reynier, Pauline; Platt, Robert W.; Filion, Kristian B.
Abstract: Purpose: Our aim was to describe trends in the prescription of domperidone for insufficient lactation in England, the characteristics of women prescribed it postpartum, and the impact of a 2014 European Medicines Agency (EMA) recommendation to restrict its use due to a potential increased risk of sudden cardiac death associated with its use. Methods: We conducted a population‐based cohort study with interrupted time series analysis using data from the Clinical Practice Research Datalink linked to Hospital Episode Statistics. We identified women with live births from 2002 to 2015, excluding those with nonlactation indications for domperidone (n = 247 349). We evaluated trends in the prescription rate of domperidone in the 6 months postpartum and differences in this rate before and after the EMA recommendation. Results: Domperidone was prescribed among 1438 deliveries at a rate of 1.24 per 100 person‐years. This rate increased from 0.56 to 2.1 per 100 person‐years between 2002‐2004 and 2011‐2013 (rate ratio: 3.8; 95% confidence interval [CI], 3.2‐4.6). Prescribing decreased in level by 0.35 (95% CI, −0.86 to 0.16) per 100 person‐years immediately following the recommendation with little change in trend (0.003; 95% CI, −0.059 to 0.065 per 100 person‐years). Following the recommendation, prescription of doses >30 mg and coprescription of drugs with a risk of torsade de pointes decreased. No arrhythmic events were observed among domperidone users. Conclusions: Although we observed an important increase in prescribing during the study period, domperidone remains infrequently prescribed postpartum in England. While overall prescribing changed little, some prescribing practices became more restricted following the EMA's recommendation.